Smart City : Upaya Pembangunan Kota Surabaya - Laili Dwi Agustina; Nur Fitri Ana Melati; Febian Ragil Prawesti; Fierda Nurany (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2023)
The city of Surabaya is trying to encourage the Smart City concept through developing adequate infrastructure, structuring an online-based government system and creating application innovations for public service processes. This research aims to analyze and study Smart City as an effort to develop the city of Surabaya. The research method used is qualitative with data collection techniques, namely interviews, observation and documentation. Data collection was carried out by compiling data obtained from LKJ and RPJDP of Surabaya City. The research results show that Bappeda Litbang plays a crucial role in implementing Smart City and Disperpusip plays a role in improving human resources in the city of Surabaya. Both OPDs have the same factors driving the success of Smart City, namely a strong commitment from the Mayor of Surabaya and policies that support developing long-term strategies related to Smart City implementation. On the other hand, the implementation of Smart City in Bappeda R&D has an impact on the HDI value of Surabaya City, which in 2019 increased by 82.22%. Meanwhile, Disperpusip has an influence on the IKM value of 95.36% with category A. Thus, the success achieved has a positive impact on the development of the City of Surabaya, so that the implementation of Smart City in the City of Surabaya does not only focus on the government, but also on cooperation and commitment from the community.